Characterization fine grained low alloy steel 22 NiMoCr 3 7 by magnetic Barkhausen noise analysis - Isnan, May; Kusuma, Gilang Cempaka; Hamdani, Hamdani; Sudasri, Imam; Kurnia, Asep; Rafi, Hanif Muzhaffar; Putra, Andhika (Institute of Advanced Engineering and Science, 2025)
To ensure the quality of mass-produced products, non-destructive material testing (NDT) is required with a method that has high testing speed and accuracy. Products that have undergone heat treatment such as automotive components to obtain a specific hardness value need to be tested to ensure the desired quality. Some parameters such as coercivity and permeability of the ferromagnetic materials, can be used to characterize the shape of the hysteresis curve. The hysteresis curve geometry is related to mechanical hardness, hot working record, and the presence of residual stresses. This paper will present how the coercivity value measurement can be done using the Barkhausen effect, as well as a study of the correlation between the coercivity value and the hardness of a ferromagnetic material using the regression analysis method. Indentation testing has also been done to verify different approaches to obtain hardness value by Barkhausen noise analysis. The research shows that this technique was sufficiently accurate with superior rapid testing and no indentation mark.